Canonical and Official Cuneiform Texts: Towards an Understanding of Assurbanipal's Personal Tablet Collection - Lieberman, Stephen J. (Fs Moran)
Table on p.324-325: Summary of Predictions for Month of Iyyar; Appendix on p.334-336: The Tablets on which CT 22,1 is based; 1 fig.